Analisis Kualitas Layanan dan Fasilitas terhadap Kepuasan Siswa menggunakan Data Mining - Wijana, Miki; Nur’aeni, Nur’aeni; Mu’minin, Ayi Mi’razul (Jurnal Maps (Manajemen Perbankan Syariah), 2025)
Based on the observations, this study was motivated by the fluctuating number of students at Al Ma’soem School during the 2021-2024 period. The purpose of this research is to determine the level of student satisfaction measured from the quality of facility services. The research method employed is quantitative associative with the support of data mining. The object of this research is the satisfaction of elementary, junior high and high school students of Al Ma'soem by using primary data and data collection techniques in the form of observations, interviews, literature studies, questionnaires and tests. The population in this study is all Al Ma'soem students as many as 2,462 students, while the sample taken is 660 students. The results obtained show that on average 81% are satisfied. Thus, the quality of facility services has a significant relationship with the level of student satisfaction. Improving facility services not only enhances student satisfaction but also supports the effectiveness of learning in the Al Ma’soem Boarding School environment.